An Ethical Literary Analysis of Edward’s Ethical Choices in The Cocktail Party - HUANG, Haowen (Pacific International Journal, 2023)
This paper examines Edward's ethical choices in T.S. Eliot's play, "The Cocktail Party," through the lens of ethical literary criticism. Edward, the protagonist, faces an emotional crisis in his relationships with his wife, Lavinia, and his lover, Celia, which sets the stage for his ethical dilemma. The study utilizes a qualitative research design, employing literary analysis and interpretation to delve deeper into Edward's ethical choices and their appropriateness within his particular situations and ethical environment. Drawing from previous scholarly work, particularly from scholars in China who have explored the ethical fables and perspectives within "The Cocktail Party," this paper builds upon the existing research by offering further insights into Edward's ethical journey. The analysis considers the interplay between Edward's marital and romantic ethical identities and his professional identity as a lawyer, which results in contradictions and conflicts, leading to ethical dilemmas. The study also explores the factors influencing Edward's ethical choices, including the disruption of ethical relationships and order within the play. By applying ethical literary criticism, the paper argues that Edward's ethical choices are not arbitrary but appropriate responses to his circumstances. Situational ethics and love norms are examined to understand the motivations and justifications behind Edward's decisions. Ultimately, the analysis provides a comprehensive exploration of the ethical themes within the play, shedding light on the complexities of decision-making processes and the moral dimensions of literary works.